Altruism and Re-Orientation as Core for the Development of Africa - Omale, Simeon; Amana, Damian (American Journal of Humanities and Social Sciences, 2014)
Jan Knippers Black in his book, Development in Theory and Practice: Paradigm and Paradoxes had identified theories ranging from Liberal international School; modernization school; cultural weakness; Interdependence School as reasons for the unparalleled development of the world. While often these are used along the like of cultural imperialism and the un-even trade opportunities as reasons for Africa’s developmental quagmire, it is the opinion of this paper that Africa’s underdevelopment are largely products of our actions and non-actions. It is in this light that we seek to argue for the development of the spirit of Altruism and a reorientation of the national consciousness via investment in the Early Child Education adopting participatory learning and communication approach as necessary panacea for Africa’s development. By instilling in the young minds the expediency of a more altruistic modus vivendi, the culture of egoistic corruption could be overturned.